SPECIAL FIELDS OF THE GALAXY RADIO EMISSION - Vasilenko, N. M.; Sidorchuk, M. A. (Одеські астрономічні публікації, 2016)
The brightness temperatures of radio emission were measured with the UTR-2 low-frequency radio telescope at frequencies 12.6, 14.7, 16.7, 20 and 25 MHz for the following Galaxy regions: the North Pole, the area of minimum radio brightness and the anticenter region. The brightness temperature spectrums of the galactic background radiation were constructed for the selected areas using the data at other different wavelengths. The brightness temperature spectral indices were determined for these areas at wavelengths ranging from meter to decameter.